Endoplasmic Reticulum Chaperones and Their Roles in the Immunogenicity of Cancer Vaccines - Graner, Michael W.; Lillehei, Kevin O.; Katsanis, Emmanuel (Frontiers in Oncology, 2015)
The endoplasmic reticulum (ER) is a major site of passage for proteins en route to other organelles, to the cell surface, and to the extracellular space. It is also the transport route for peptides generated in the cytosol by the proteasome into the ER for loading onto major histocompatibility complex class I (MHC I) molecules for eventual antigen presentation at the cell surface. Chaperones within the ER are critical for many of these processes; however, outside the ER certain of those chaperones may play important and direct roles in immune responses. In some cases, particular ER chaperones have been utilized as vaccines against tumors or infectious disease pathogens when purified from tumor tissue or recombinantly generated and loaded with antigen. In other cases, the cell surface location of ER chaperones has implications for immune responses as well as possible tumor resistance. We have produced heat shock protein/chaperone protein-based cancer vaccines called “CRCL” (Chaperone-Rich Cell Lysate) that are conglomerates of chaperones enriched from solid tumors by an isoelectric focusing technique. These preparations have been effective against numerous murine tumors, as well as in a canine with an advanced lung carcinoma treated with autologous CRCL. We also published extensive proteomic analyses of CRCL prepared from human surgically-resected tumor samples. Of note, these preparations contained at least ten ER chaperones and a number of other residents, along with many other chaperones/heat shock proteins. Gene ontology and network analyses utilizing these proteins essentially recapitulate the antigen presentation pathways and interconnections. In conjunction with our current knowledge of cell surface/extracellular ER chaperones, these data collectively suggest that a systems-level view may provide insight into the potent immune stimulatory activities of CRCL with an emphasis on the roles of ER components in those processes.